The first galaxies in the Hubble Frontier Fields - Bhatawdekar, Rachana (2019)
In this thesis we have exploited the power of gravitational lensing of massive clusters to probe galaxy evolution with the galaxy stellar mass functions (GSMF) and UV luminosity functions (UV LF) at $z=6-9$. Throughout the thesis the data utilized is from the Hubble Frontier Fields (HFF) program.